URUKUT - diário escolar para escolas municipais do médio e baixo Amazonas - Rossy, Rickson Brandão (Brasil, 2024)
Information and Communication Technologies are widely used in people's communication, business development, and even in the educational field. Furthermore, technological resources enable the automation of business, education, and scientific research processes. In this context, this work aims to develop a School Diary tailored for public municipal educational institutions to assist with management in monitoring attendance, grades, and lesson plans in municipal schools within the Amazonas region. The methodology employed was based on a literature review, followed by the development of the School Diary software, using tools such as Firebase to manage the database. This allows for the utilization of a development ecosystem that can be adapted to various platforms and optimized for regions with limited connectivity. Finally, a software evaluation was conducted. The results of the evaluation demonstrate the level of acceptance of the developed software, along with the contributions of the participants regarding accessible software solutions for schools in remote areas.